PENGARUH KOMPENSASI DAN KOMITMEN ORGANISASIONAL TERHADAP TURNOVER INTENTION PENDIDIK KELOMPOK BERMAIN PADA LEMBAGA PENDIDIKAN ANAK USIA DINI (PAUD) DI KOTA MATARAM - Hendra Yuliana (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
This study was conducted to determine the effect of compensation and organizationalcommitment to turnover intention Educators Play Group at the Institute for Early ChildhoodEducation ( ECD ) in Mataram . The method of data collection is a sample survey and the populationin this study were all early childhood educators in play group in Mataram . The sample wasdetermined using random probability sampling technique with a total sample is 85 people . Theanalytical tool used to process the data and test the hypothesis is multiple linear regression .The results showed that compensation has a significant influence on turnover intention aswell as the commitment of the organization to have a significant effect on turnover intention . Effectof compensation and significant organizational commitment on the partial test or simultaneously .Compensation is more variable than the dominant influence of organizational commitment .Keywords : Compensation , Organizational Commitment , Turnover Intention